PENERAPAN RESTORATIVE JUSTICE TERHADAP PELAKU TINDAK PIDANA PERUSAKAN BARANG (STUDI DI KEJAKSAAN NEGERI SERDANG BEDAGAI) - Elon Unedo Pinondang; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
The law enforcement process recognizes the settlement of criminal cases by prioritizing restorative justice, which emphasizes restoration to its original state, in order to create a balance of protection so that the interests of victims and perpetrators of crimes are not only oriented towards retaliation, but rather towards efforts to settle cases outside the court. . but the application of restorative justice is still something new in Indonesian society, and in practice there are still many obstacles by law enforcers to seek restorative justice. law enforcement efforts in implementing restorative justice against perpetrators of criminal acts of damage to goods and obstacles to restorative justice against perpetrators of criminal acts of destruction of goods. Based on the research results, it is known that in implementing restorative justice, the Attorney General's Office issued RI Attorney Regulation No. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. If a crime occurs, and the efforts of law enforcers to apply restorative justice to the perpetrators of criminal acts of damage to goods, the prosecutor as law enforcer has the right to terminate the prosecution based on Perja No. restorative justice. 15 of 2020, and the obstacles to restorative justice for perpetrators of criminal acts of damage to goods are internal and external obstacles.